Synthesis and biological activity of desmethoxy analogues of coruscanone A - Vostatková, Lucie; Matoušová, Eliška; Špulák, Marcel; Kuneš, Jiří; Votruba, Ivan; Buchta, Vladimír; Pour, Milan (Bioorganic & medicinal chemistry letters, 2011)
A series of simple desmethoxy analogues of coruscanone A was prepared via a novel version of Ti(iPrO)(4)-mediated Knoevenagel condensation of cyclopentenedione with substituted benzaldehydes and cinnamic aldehydes, and the compounds were evaluated for antifungal activity and cytotoxicity. The most potent 2-benzylidenecyclopent-4-ene-1,3-dione possessed antifungal effect comparable to coruscanone A and a somewhat broader spectrum of activity against Candida species. The compound was also superior to fluconazole against several non-albicans Candida sp. Evaluation of the ability of the compound to influence cell proliferation using two different assays showed that 2-benzylidenecyclopent-4-ene-1,3-dione has lower cytotoxicity compared to the natural product.
Keywords: vztahy mezi strukturou a aktivitou; buněčné linie; Humans; Structure-Activity Relationship; Cell Line; nádorové buněčné linie; Mice; zvířata; kandidóza; Microbial Sensitivity Tests; mikrobiální testy citlivosti; Antifungal Agents; cyklopentany; Candida; gama-butyrolakton; antifungální látky; 4-Butyrolactone; Candidiasis; myši; Animals; lidé; Cyclopentanes; Cell Line, Tumor